Recording and verification of educational documents in schools of Lviv City with the help of designing of information and reference system - Bilushchak, Тetiana; Yaschyshyn, Iryna (Turystyka i Rozwój Regionalny, 2017)
The article deals with the problem of introduction students’ recording and verification of personal data for the issuance of a duplicate in the case of loss of educational documents. The authors propose to change the manual search technology to the electronic by designing the information system on the basis of the Access DB program. The proposed database contains a convenient system interface, reports, macros, the ability of creating queries and issuance references based on the found information.